Regionalism and Regional Integration in South America: A discussion on the difficulties and ideological divergences (2000-2016) (Terr@ Plural, 2022)
This paper analyzes the regional integration in South America and discusses the main difficulties and obstacles until 2016. During the 2000s, with the so-called Pink Tide, there was the rise of several left-wing and center-left governments in the region, which were dedicated to formalizing regional integration initiatives to project South America as a center of power on the international scene. However, these initiatives were not homogeneous in their ideological aspects, generating some contrasts between them. Also, with the decline of the left-wing and center-left governments in the region between 2011 and 2016, the initiatives gradually weakened, causing a setback to regional integration in the subcontinent.
Keywords: Regional Initiatives; Region; Antagonism